Health Education Management Strategies to Achieve Stunting Reduction Targets in Minahasa Regency - Ivonny M. Sapulete; Deitje A. Katuuk; Ruth Umbase; Joseph Philip Kambey (JR Education, 2026)
This article analyzes health education management strategies for accelerating the reduction of stunting in Minahasa Regency. The study is positioned within educational management because stunting reduction is not only a biomedical intervention but also a managed learning process that requires planning, role distribution, community education, inter-sector coordination, monitoring, and sustainability. A qualitative design was used through in-depth interviews, focus group discussions, and document review involving health workers, posyandu cadres, and affected community members. The findings show that health services for stunting reduction have been implemented through primary health care channels such as puskesmas, posyandu, and referral services. The services include antenatal care, iron supplementation, supplementary feeding, immunization, growth monitoring, nutrition education, and follow-up for children with nutritional problems. However, the target has not been fully achieved because stunting remains a multidimensional problem shaped by socioeconomic conditions, cultural practices, incomplete behavior change, limited human resources, fragmented data, and weak cross-sector integration. The article proposes an integrated health education management model consisting of Division of Work, Promotive Education, Preventive Action, Life-Cycle Approach, Community-Based Action, Integrated Services, and Sustainability. The model contributes to educational management by framing stunting reduction as a coordinated system of learning, behavior change, and public health governance.